Settlement deservingness perceptions of climate change, economic, and political migrant groups across partisan lines - Defne Aksit; Tijs Laenen (Frontiers in Sociology)
International migration is a prevailing issue of our times. With opponents of multicultural societies becoming more vocal across Europe, it is pivotal to strengthen our knowledge of how migrants are popularly perceived in receiving countries. Prior research suggests that there is remarkable agreement within different countries as to which types of migrants are seen as deserving of settlement, cutting across deep-rooted partisan divides. Building on the CARIN deservingness theory, this article sheds new light on this so-called “hidden immigration consensus” by investigating Americans’ original perceptions of different migrant groups rather than following the standard practice of assessing how they react to a set of pre-defined migrant characteristics in a conjoint experiment. Based on a split-sample experiment, our results show that liberals and conservatives significantly differ in their perceptions of political, economic, and climate change migrants on four of the five CARIN criteria. Liberals differentiate between migrants on control, attitude, and identity criteria, whereas conservatives only distinguish on the control criterion. Liberals rate all migrant groups twice as deserving as conservatives. The implications for the settlement deservingness model and the hidden consensus hypothesis are discussed.